Topics in Modal Analysis & Testing, Volume 9 Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics 2018 - Mains, Michael; Dilworth, Brandon J. (Conference Proceedings of the Society for Experimental Mechanics Series, 2019)
Topics in Modal Analysis & Testing, Volume 9: Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics, 2018, the ninth volume of nine from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Modal Analysis, including papers on: Operational Modal & Modal Analysis Applications Experimental Techniques Modal Analysis, Measurements & Parameter Estimation Modal Vectors & Modeling Basics of Modal Analysis.